Ensavaged writing, combative writing : an ethnocritic of Victor Hugo's early novels - Dumoulin, Sophie (HAL CCSD, 2013)
Texte intégral accessible uniquement aux membres de l'Université de Lorraine jusqu'au 2028-01-01 This thesis explores the ethnocultural world of Victor Hugo's first novels: Hans of Iceland (1823), Bug-Jargal (1826), The Last Day of a Condemned Man (1829) and The Hunchback of Notre-Dame (1831). It appears that recurrent motifs in this early writing form a symbolic architecture that can be understood to follow two main cultural structures: the dialectics of literacy/orality and Carnival/Lent. Both structures underpin the narrative and fictional organization of each novel, while they construct throughout the corpus a general dynamic of order/disorder antinomy. Following an ethnocritical approach (V. Cnockaert, J. M. Privat, M. Scarpa), we look into the question of rites and customs considered as ethnographic signs, and examine their modes of integration in the fictional fabric. On the one hand we study the connections between what is related to the logic of Lent - the Institutions, which enforce an order mainly based on oppressive regimes - and what is related to the Carnivalesque (or the common practices of traditional Carnivals) - the characters of disturbance, who are all destined for singular fates. And on the other hand, we demonstrate how these ethnologic references are part of a larger scheme, generating cultural belligerencies between literacy and orality. Our thesis also seeks to shed light on what this cultural plurality brings to Hugo's writing, a writing which lays claim to change and social revolution. Readapted by the author, transformed by and in the writing, the cultural structures indeed get a new meaning in the work's constituent system of relations (Bourdieu). Therefore not only do they give rise to what Bakhtine calls a -carnavalisation littéraire -, but they set up a unifying coherence in our corpus. The polyphonic range of the ensavagement effects generated by this carnivalesque writing -where opposite cultural elements are confronted and sometimes crossbred - allows us to put forward an ...